Within the City: Ongoing Experiences in Local Urban Development Plans - Benelli, Federica; Magaudda, Stefano (International Studies. Interdisciplinary Political and Cultural Journal, 2017)
The article presents a series of urban regeneration programmes carried out in the Lazio Region from 2011 to 2016, and financed by the resources of the cohesion policy 2007–2013. It covers: programme background, experience of the Municipality of Aprilia analysed in its most relevant details, some reflections concerning opportunities and limits of the programme, and some key elements to be developed in future research.